Microsoft Dynamics GP 2010 cookbook : solve real-world Dynamics GP problems with over 100 immediately usable and incredibly effective recipes /: solve real-world Dynamics GP problems with over 100 immediately usable and incredibly effective recipes. (©2010) - Unknown
No abstract available